Which is the ideal JAK inhibitor for alopecia areata - Baricitinib, tofacitinib, ritlecitinib or ifidancitinib - Revisiting the immunomechanisms of the JAK pathway - Kabir Sardana; Savitha Bathula; Ananta Khurana (Wolters Kluwer Medknow Publications, 2023)
Alopecia areata (AA) is an immune-mediated condition, clinically manifesting as non-cicatricial patches of alopecia. It is often a self-limiting condition; however, regrowth of hair can take a long period of time, resulting in significant psychological comorbidity. With the recent advances in pathomechanisms of AA, the therapeutic approach to the condition has become more specific, and targeted therapy with small molecules is probably the ideal intervention. Many therapies exist for AA, but none of the systemic agents were approved, until recently, when baricitinib (Janus kinase (JAK1 and JAK2 inhibitor) gained FDA approval for the treatment of adult patients with severe AA. JAK inhibitors (JAKibs) target the γc cytokine and interferon-gamma (IFN-γ) signaling pathway, which is critical to the immunopathogenesis of AA and thus can reverse the hair loss in AA. Although JAKibs are emerging as a promising treatment modality for AA, the ideal JAKib is not yet settled, as there is scant data on H-2-H (head-to-head) comparisons of JAK inhibitors in AA. Moreover, the response achieved with JAKibs is not sustained after treatment discontinuation, with many studies showing a high recurrence rate with tofacitinib and ruxolitinib post-treatment. Also, recent studies have hypothesized that JAK2, with its ubiquitous expression, can cause adverse effects, unlike JAK1, which is associated with multiple major cytokine receptor families and JAK3, which is exclusively associated with the γc cytokine receptor. Thus, JAK3ibs may be associated with a better side effect profile and, in conjunction with their specificity, may replace other JAKibs as the treatment of choice for AA. We herein discuss the role of the JAK/STAT (signal transducer and activator of transcription) pathway in AA, the intricacies of various JAKibs in the management of AA, and emphasize the need for studies on tissue JAK and cytokine expression before arriving at the ideal JAKibs for AA.